2020
DOI: 10.3390/s20071946
|View full text |Cite
|
Sign up to set email alerts
|

GMPSO-VMD Algorithm and Its Application to Rolling Bearing Fault Feature Extraction

Abstract: The vibration signal of an early rolling bearing is nonstationary and nonlinear, and the fault signal is weak and difficult to extract. To address this problem, this paper proposes a genetic mutation particle swarm optimization variational mode decomposition (GMPSO-VMD) algorithm and applies it to rolling bearing vibration signal fault feature extraction. Firstly, the minimum envelope entropy is used as the objective function of the GMPSO to find the optimal parameter combination of the VMD algorithm. Then, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 45 publications
0
29
0
Order By: Relevance
“…Therefore, it is necessary to set the appropriate α and K through the optimization algorithm. In this paper, the selection range of α is [50, 3500], and the selection range of K is [2,12].…”
Section: Multi-objective Multi-island Genetic Algorithm Optimizes the Parameters Of Vmdmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is necessary to set the appropriate α and K through the optimization algorithm. In this paper, the selection range of α is [50, 3500], and the selection range of K is [2,12].…”
Section: Multi-objective Multi-island Genetic Algorithm Optimizes the Parameters Of Vmdmentioning
confidence: 99%
“…Figure 12 shows the change process of fitness values of signals under four rotational speed conditions with the increase of iterations in the optimization process. Finally, the VMD optimal parameter combinations [K 0 , α 0 ] of signals under four rotational speed conditions are found as [11,350], [10,3236], [11,750], [12,501]. According to the optimal parameter combination [K 0 , α 0 ], the VMD parameters of signals under four rotational speed conditions are set and the signal is decomposed by VMD.…”
Section: 45mentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, to optimally select the parameter K of VMD, the genetic variation sample group, kurtosis criterion variational mode decomposition, and self-organizing mapping (SOM) neural network have been adopted to adaptively determine the optimal value of the parameter K in [9][10][11][12]. To verify the effectiveness of these new methods, some experiment examples have been used to simulate in [13][14][15][16][17]. e simulated results showed that these improved models may solve the shortcomings to a certain extent.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers used an optimization algorithm to optimize the parameter combination of the penalty factors and the number of decomposition in the VMD decomposition process. e genetic mutation particle swarm optimization (GMPSO) algorithm to optimize the VMD algorithm parameters is utilized by Ding [12,13]. Experimental results show that he GMPSO-VMD algorithm has a good decomposition effect on the gear fault signal.…”
Section: Introductionmentioning
confidence: 99%